Thermofield quantum electrodynamics in (1 + 1) dimensions at a finite chemical potential: a bosonization approach: a bosonization approach - Amaral, R. L. P. G.; Belvedere, Luiz Victorio; Rothe, Klaus D. (Journal of physics. A, Mathematical and theoretical, 2011)
The recent generalization of the Lowenstein-Swieca operator solution of quantum electrodynamics in (1+1) dimensions to a finite temperature in thermofield dynamics is further generalized to include a non-vanishing chemical potential. The operator solution to the Euler-Lagrange equations respecting the Kubo-Martin-Schwinger condition is constructed. Two forms of this condition and their associated solutions are discussed. The correlation functions of an arbitrary number of chiral densities are computed in the thermal θ-vacuum.